Impact of the Implementation of a Bovine Viral Diarrhea Virus Targeted Vaccine in Dairy Farms: Longitudinal Analysis - Bellido, Demian; Wenz, Diego; Schang, Martin; Rubiolo, Facundo Tibaldo; Mangioni, Pablo; Gumina, Emanuel; Wigdorovitz, Andres; Parreño, Viviana (MDPI, 2025)
Objective: This study evaluated the effect of a novel subunit-targeted vaccine against BVDV in six dairy farms in Argentina. Methods: Reproductive, health, and production parameters—including conception and abortion rates, open days, calves born per insemination, as well as newborn and overall mortality, and milk production—were monitored over a ten-year period (2014–2023). Data were analyzed annually to assess trends and compare the periods before and after vaccine introduction. Results: All parameters showed significant improvement after vaccine incorporation, with an 11% increase in conception rate, a 5% reduction in abortion rate, a 12% increase in calves per insemination rate, and a decrease of 11 open days (8.4%). Additionally, newborn mortality and overall mortality decreased by 33% and 16%, respectively, while milk production increased by 9%. These data were also compared with eight non-vaccinated dairy farms, and significant differences were observed in health and reproductive parameters. Conclusions: These findings indicate that vaccination with an effective non-replicating subunit vaccine can successfully minimize the impact of BVDV in dairy farms.